Developing the FEEDS toolkit of parent-delivered interventions for eating, drinking and swallowing difficulties in young children with neurodisability: findings from a Delphi survey and stakeholder consultation workshops. Issue 1 (29th April 2022) - Taylor, Helen; Pennington, Lindsay; Morris, Christopher; Craig, Dawn; McConachie, Helen; Cadwgan, Jill; Sellers, Diane; Andrew, Morag; Smith, Johanna; Garland, Deborah; McColl, Elaine; Buswell, Charlotte; et al.
Abstract : Background: Young children with neurodisability commonly experience eating, drinking and swallowing difficulties (EDSD). Little is documented about which interventions and outcomes are most appropriate for such children. We aimed to seek consensus between parents of children with neurodisability and health professionals on the appropriate interventions and outcomes to inform future clinical developments and research studies. Methods: Two populations were sampled: parents of children aged up to 12 years with neurodisability who experienced EDSD; health professionals working with children and young people (aged 0–18 years) with neurodisability with experience of EDSD. Participants had taken part in a previous national survey and were invited to take part in a Delphi survey and/or consultation workshops. Two rounds of this Delphi survey sought agreement on the appropriate interventions and outcomes for use with children with neurodisability and EDSD. Two stakeholder consultation workshops were iterative, with the findings of the first discussed at the second, and conclusions reached. Results: A total of 105 parents and 105 health professionals took part. Parents and health professionals viewed 19 interventions and 10 outcomes as essential. Interventions related to improvement in the physical aspects of a child's EDSD, behavioural changes of the child or parent, and changes in the child or family's well-being. Both parents and health professionals supported a 'toolkit' of interventions that they could use together in shared decision making to prioritise and implement timely interventions appropriate to the child. Conclusions: This study identified interventions viewed as essential to consider for improving EDSD in children with neurodisability. It also identified several key outcomes that are valued by parents and health professionals. The Focus on Early Eating, Drinking and Swallowing (FEEDS) Toolkit of interventions to improve EDSD in children with neurodisability has been developed and now requires evaluation regarding its use and effectiveness.